2004
DOI: 10.1111/j.1365-2141.2004.05288.x
|View full text |Cite
|
Sign up to set email alerts
|

Darbepoetin alpha for the treatment of anaemia in low‐intermediate risk myelodysplastic syndromes

Abstract: Summary Thirty‐seven anaemic subjects with low‐to‐intermediate risk myelodysplastic syndrome (MDS) received the highly glycosylated, long‐acting erythropoiesis‐stimulating molecule darbepoetin‐alpha (DPO) at the single, weekly dose of 150 μg s.c. for at least 12 weeks. Fifteen patients (40·5%) achieved an erythroid response (13 major and two minor improvements, respectively, according to International Working Group criteria). Such results are currently maintained after 7–22 months in 13 of the responders, one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
70
0
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(76 citation statements)
references
References 25 publications
(32 reference statements)
5
70
0
1
Order By: Relevance
“…There were too few studies for meaningful stratified analyses in any category except for study duration. The study with the longest duration (Ͼ20 weeks) of darbepoetin use [25] had a higher Hb response rate (55.8%) than the study [24] with the shortest duration (12 weeks) of darbepoetin use (40.0%). None of the darbepoetin studies reported use of concomitant iron.…”
Section: Efficacy Of Esps In Mdsmentioning
confidence: 87%
See 2 more Smart Citations
“…There were too few studies for meaningful stratified analyses in any category except for study duration. The study with the longest duration (Ͼ20 weeks) of darbepoetin use [25] had a higher Hb response rate (55.8%) than the study [24] with the shortest duration (12 weeks) of darbepoetin use (40.0%). None of the darbepoetin studies reported use of concomitant iron.…”
Section: Efficacy Of Esps In Mdsmentioning
confidence: 87%
“…The most frequently reported significant predictor was baseline serum erythropoietin level, with low levels predicting response to exogenous ESPs ( [24,25,31,32]. Low pretrial transfusion needs were also predictive of ESP response, in three studies [24,31,32].…”
Section: Efficacy Of Esps In Mdsmentioning
confidence: 98%
See 1 more Smart Citation
“…Although increased erythroid responses have been noted with the addition of GCSF to EPO as well as with increased EPO doses (Greenberg et al, 2009b), a meta-analysis of data using these regimens demonstrated higher responses with the drug combination mainly in patients with relatively lower dose EPO monotherapy (Mundle et al, 2009). Darbepoetin (a longer acting version of EPO) has demonstrated similar and perhaps improved efficacy at doses of 150-300 lg sc every 1-2 weeks (Musto et al, 2005;Stasi et al, 2005;Mannone et al, 2006;Gotlib et al, 2008).…”
Section: Management Of Lower Risk Diseasementioning
confidence: 99%
“…17,18 The phase II study reported a response rate of 60%, with few additional responses when G-CSF was added. Further studies are needed to explore the long-term activity of darbepoetin as well as the optimal dosing schedules.…”
Section: Hemopoietic Growth Factorsmentioning
confidence: 99%